2002
DOI: 10.1021/jf0116202
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in Vitro Biological Activities of Hop Proanthocyanidins:  Inhibition of nNOS Activity and Scavenging of Reactive Nitrogen Species

Abstract: Oligomeric proanthocyanidins constitute a group of water-soluble polyphenolic tannins that are present in the female inflorescences (up to 5% dry wt) of the hop plant (Humulus lupulus). Humans are exposed to hop proanthocyanidins through consumption of beer. Proanthocyanidins from hops were characterized for their chemical structure and their in vitro biological activities. Chemically, they consist mainly of oligomeric catechins ranging from dimers to octamers, with minor amounts of catechin oligomers containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 47 publications
1
68
0
3
Order By: Relevance
“…A similar type of mixed inhibition was observed in cardiovascular drugs and benzodiazepines against BuChE (Chiou et al, 2005). Several reports have shown that green tea catechins and its derivatives exhibited potent neuroprotective effect in AD by attenuating oxidative stress and inflammatory mediated damage (Stevens et al, 2002;Sutherland et al, 2006). Recent studies have shown that green tea catechins enhance cholinergic function by inhibiting AChE activity and prevent neuronal damage by effectively blocking the aggregation of Ab peptide (Okello et al, 2012;Wang et al, 2012).…”
Section: Characterization Of Compoundmentioning
confidence: 54%
“…A similar type of mixed inhibition was observed in cardiovascular drugs and benzodiazepines against BuChE (Chiou et al, 2005). Several reports have shown that green tea catechins and its derivatives exhibited potent neuroprotective effect in AD by attenuating oxidative stress and inflammatory mediated damage (Stevens et al, 2002;Sutherland et al, 2006). Recent studies have shown that green tea catechins enhance cholinergic function by inhibiting AChE activity and prevent neuronal damage by effectively blocking the aggregation of Ab peptide (Okello et al, 2012;Wang et al, 2012).…”
Section: Characterization Of Compoundmentioning
confidence: 54%
“…Hop extracts and/or compounds have been reported to be "active" or the equivalent by the authors of the given studies in the following assays: various antioxidant and/or chemoprevention (Gerhäuser et al, 2002;Gerhäuser et al, 2001;Liegeois et al, 2000;Masaki et al, 1995;Oyaizu et al, 1994;Stevens et al, 2002;Tagashira et al, 1995), antimicrobial, particularly against Gram positive bacteria (Grange and Davey, 1990;Langezaal et al, 1992;Matos et al, 2001;Ohsugi et al, 1997;Racz et al, 1980;Simpson and Smith, 1992;Tagashira et al, 1997), and cytotoxicity (Bae et al, 1996;Liu et al, 2001;Miranda et al, 1999;Shipp et al, 1994). Many constituents have been reported from hops (Farnsworth, 2003), among which in addition to the aforementioned estrogenic properties, many have been shown to possess other types of biological activity (Honma et al, 1998;Shipp et al, 1994;Tabata et al, 1998;Tobe et al, 1995;Tobe et al, 1997;Yasukawa et al, 1995) such as potential cancer chemopreventive activity (Gerhäuser et al, 2001a;Miranda et al, 2000a) and suppression of COX-2 gene transcription (Yamamoto et al, 2000).…”
Section: Other Activitiesmentioning
confidence: 99%
“…Procyanidins have been reported to exhibit a variety of biological activities, including strong antioxidative or free radical scavenging effects, 29,30) inhibition of nitric oxide synthase (nNOS), 31) anti-inflammatory and pigmentation inhibition, 9) anti-cataract effects in diabetic rats, 32) anti-tumor-promotion, 33) inhibition of melanogenesis in B16 mouse melanoma cells, 34) secretion of interleukin-5 in peripheral blood mononuclear cells, 35) and inhibition of cellular adherence and water-insoluble glucan synthesis of mutans Streptococci.…”
mentioning
confidence: 99%